Correlation Between Docosahexaenoic Acid Intake and It’s Content in Breast Milk of Lactating Mothers in Jakarta - Raphael Kosasih; Ninik Mudjihartini; Saptawati Bardosono (World Nutrition Journal, 2020)
Objective: Docosahexaenoic acid (DHA) is the predominant structural fatty acid in the brain and crucial for cognitive development in early life. Newborn DHA intake completely depends on preformed DHA in mother’s breast milk. In advancing years, globalization has been declining the fish intake of Asian countries. This study aims to determine DHA intake among lactating mothers in Jakarta and its association with breast milk’s DHA.Method: This cross-sectional study was conducted in Grogol Petamburan and Cilincing Public Health Centers, Jakarta. Eighty healthy lactating mothers aged 20–35 years old in 1–6 months postpartum were taken using consecutive sampling method. Characteristics data were taken by interviews and DHA intake was assessed with the semiquantitative food frequency questionnaire. Breast milk specimens were collected in the morning and its DHA content was analyzed using Gas Chromatography with Mass Spectrometry. Descriptive analyses and Spearman rho test were used with a 95% confidence level.Result: This study showed the median of subjects’ DHA intake was 158.5(13.9–719.7) mg/day, i.e., 67.5% of the subjects was below Food and Agriculture Organization (FAO) recommendation. The median of breast milk DHA was 51.7(19–184.7) mg/day, only 42.5 % of the subjects had breast milk DHA to meet the minimal requirement of their infant. A moderate positive correlation was found between maternal DHA intake with breast milk DHA (r = 0.478, p < 0.001). Conclusion:  Maternal DHA intake has moderate positive correlation with breast milk DHA, more than half of the subject had DHA intake below FAO recommendation.